Stewardship: A Biblical Model for the Formation of Christian Scholars - Smith, Julien (Journal of education & Christian belief, 2013)
THIS ARTICLE EXPLORES theological dimensions of the academic vocation, taking its cue from the research undertaken by the Carnegie Initiative on the Doctorate, which envisions the scholar as a steward of an academic discipline. We contend, however, that the Christian scholar's sense of stewardship extends beyond one's academic discipline to encompass the Christian faith as well. Both the creation account in Genesis and the parable of the entrusted money in the Gospels illuminate three vital aspects of Christian scholarship: generation, conservation, and transformation. The article culminates in a discussion of formation or transformation of doctoral students preparing for the academy, with practical examples to illustrate.